(untitled) (Ibrahim Cardiac Medical Journal, 2022)
Background & objective: Intertrochanteric fractures are becoming increasingly common as our population ages. These fractures typically occur in frail patients with multiple comorbidities The morbidity associated with the fracture can be minimized by choosing appropriate fixation device for the fracture pattern, recognizing the stability of fixation, and performing accurate reduction with ideal implant placement. So, these fractures should be treated expeditiously so that there are minimum fixation failures. In BIRDEM hospital a large number of elderly patients having intertrochanteric femur fractures with multiple comorbidities, are treated by primary hemiarthroplasty. The purpose of this study is to see the clinical outcome of these hemiarthroplasty patients. Methods: This retrospective study was carried out over four years from 2015 to 2019 on 60 patients (42 females and 18 males). All patients had diabetes in common along with other co-morbidities like ischaemic heart disease, hypertension, chronic kidney disease and stroke. The outcome was evaluated by applying Harris Hip Score after intervention. Result: The mean age of the patients was 65.5 years (range: 60-85 years) with male to female ration being 3:7. The mean Harris Hip score at the four-year follow-up was 83.1 ± 10.9. A total of 12(20%) patients were graded as excellent, 30(50%) patients as good, 15(25%) as fair and 3(5%) as poor. It was observed that, patients with AO (Arbeitsgemeinschaft für Osteosynthesefragen) type 31A1 intertrochanteric fractures had better outcome than AO type 31A2 and 31A3 in our study. Conclusion: Primary hemiarthroplasty can provide a stable, pain-free, mobile joint with acceptable complication rates. These fractures must be treated considering patient’s age, bone quality and type of the fracture. Ibrahim Card Med J 2021; 11 (1): 35-40